Hubungan Antara Perilaku Overprotective Orang Tua Terhadap Perkembangan Psikologis Pada Anak Usia Dini - Ardhea Rizka Mumtadzah; Deni Febrini; Fatrica Syafri (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to determine the relationship between parental overprotective behavior on psychological development in early childhood in Arkarami housing, Sukarami Village, Selebar District, Bengkulu City. The method used in this research is quantitative. Collecting data using a questionnaire technique. Data analysis using quantitative analysis techniques. The results showed that the calculated r was 0.690 > r table at df = 28 was 0.374, so it can be concluded that the X and Y variables have a significant relationship. Thus, the hypothesis (Ha) which reads that there is a significant relationship between parents' overprotective behavior on psychological development in early childhood in Arkarami Housing, Sukarami Sub-district, Selebar District, Bengkulu City is proven and acceptable.